Experimental study of suction-monitored CBR test on sand-kaolin clay mixture - Purwana, Y.; Nikraz, Hamid; Jitsangiam, Peerapong (The Geomate International Society, 2012)
Conventional laboratory CBR test has been widely used for predicting bearing capacity of subgrade layer for pavement design. In unsaturated soil, suction is one of the key parameters for understanding the soil behavior. The analysis of CBR is commonly presented in CBR-water content relation. The information of CBR based on soil suction is very rare and more study is still required. This paper presents a laboratory experiment of CBR test with direct suction measurement. Suction-monitored CBR test is introduced by attaching tensiometers on CBR mold and its surcharge. The standard compacted test on various proportions of sand-kaolin clay mixtures starting from 0% (pure sand), 5%, 10%, and 20% of clay were used. The tests were performed with different value of water content in both soaked and unsoaked conditions. The results indicated that the CBR versus matric suction forms a bi-linear curve. The discussion is presented in term of CBR-water content and CBR-matric suction relation.